Logística e ganhos de eficiência no serviço de transporte de cargas agropecuárias: tendências para a economia brasileira - Asai, Guilherme Augusto (2019)
This work relates agriculture, logistics and economics all at once. Given the importance of agriculture for the national economy, logistics represents a link between communication and product disposal, having the transportation services for agricultural and livestock, direct importance in regional economy’s performance. This theme is representative in a scenario of high agricultural productivity with high export rates, especially agricultural commodities, generating positive trade balance and attracting foreign currency. By combining agricultural and livestock, transportation services and economy, it was intended, throughout this work, answering what would be the trends for Brazilian economy given some change in efficiency at cargo transportation service. To complete this question, there are two hypotheses: (i) logistics is, in fact, a limiting factor for the development of Brazilian economy; and (ii) investments made are compatible with the current logistical needs. This is a descriptive research of quantitative nature, focused on database analysis and simulation of economic scenarios. The methodology used was structuring a regionalized computable general equilibrium model for the five Brazilian macro-regions, with the disaggregation of transportation services. Through the transport efficiency shocks, there was a trend of improvement in GDP, welfare, value of production, export and import in the agricultural a livestock sectors and for all the macro-regions. However, the current level of investment, in order to reduce logistical bottlenecks, is not consistent with their needs, which can lead some loss of comparative and competitive advantage.